Exploring the Competency Gap of it Students in Thailand: The Employers' View of an Effective Workforce - Siddoo, Veeraporn; Sawattawee, Jinda; Janchai, Worawit; Yodmongkol, Pitipong (Journal of Technical Education and Training, 2017)
Adapting to the digital economy is part of the national agenda in many countries. Developing IT workforces to support business growth and innovation in Thailand is now a matter of urgency. Universities which are directly responsible for producing graduates for the employment market lack direction in designing curricula because they lack understanding of industry requirements. The absence of industrial demand research leads to a loss of opportunity to develop skills within the country's working population and to maximize productive employment. The study described in this paper focused on IT internship students' competencies and aimed to analyze the gap in information technology competencies between employers' expectations and their assessment of the current competencies of intern students they employ, and to analyze the important areas which make up an effective IT student from the employers' perspective. The digital competence framework and the information technology competency model were modified to generate a structured questionnaire comprising closed-ended items, which was sent to organizations that are collaborating on work-integrated learning programs with universities in Thailand. Descriptive statistics, correlation and regression analysis were used as the analysis tools. The results found that employers' highest expectations were in respect of the self-effectiveness competency and that students do not meet their expectations in that area. However, the interns exceed the employers' expectations in respect of workplace ability and industry-wide core IT foundation skills. The regression models constructed suggested that the performance of IT students in the academic literacy and workplace ability competencies were most predictive of the average level of employers' expectations. The findings from this empirical study can be used by universities to support curriculum reform in order to meet industry requirements and by students who need to be aware of employers' needs in order to prepare themselves for employment in the IT industry.